Advances in Photoinduced Minisci-like Reactions - Martos, Mario; Bosque, Irene; Gonzalez-Gomez, Jose C. (Synthesis, 2024)
The Minisci reaction, which has been around for more than five decades, is still the preferred tool for the straightforward alkylation of basic heteroarenes. The recent developments in photocatalysis have opened novel pathways for radical generation under milder and more sustainable conditions. Implementing this approach into the Minisci reaction has renewed interest in this transformation, which is attractive per se in Medicinal Chemistry. Aspects such as sacrificial oxidants, catalysts, and specific reaction conditions should be carefully examined to evaluate the practicability of the protocol. This short review focuses on recent advances (2020 to February 2024) in photoinduced Minisci-type reactions, emphasizing sustainability.1 Introduction2 Using Noble-Metal-Based Photocatalysts3 Noble-Metal-Free Methods Using Sacrificial Oxidants4 Noble-Metal-Free Methods Without Sacrificial Oxidants5 Conclusions and Perspectives
Keywords: Minisci reaction; photocatalysis; visible light; azaarenes; free radicals